Teachers’ Strategies in Teaching English: The Impact of the Strategies Used by English Teacher to ADHD Students - Adeliah Syam; Syarifuddin Dollah; A. Muliati (International Journal of Language, Education, and Literature, 2025)
Teaching English to ADHD students is certainly not an easy task. The characteristics of ADHD students, such as being very active, having difficulty focusing, and struggling to control their emotions, present unique challenges for teachers when teaching English in the classroom. Therefore, knowledge of appropriate teaching strategies for ADHD students is essential for teachers. This thesis aims to examine the impact of the strategies used by English teacher on the ADHD students. This research design uses case study qualitative methods. The subject of this study are 3 teachers consists of main teacher and two support teachers who teach ADHD students in grade 6 of Athirah Islamic Elementary School. Data collection was conducted through non-participant observation and semi-structure interview. Based on the preliminary observation, the researcher found strategies used by teachers are, structured environment, visual aids, interactive learning, immediate feedback, frequent breaks, differentiated instruction, and co-teaching. The results of this study reveal a positive effect on ADHD students, including improve academic performance, better behavioral management, and increased focus and engagement in the learning process. This study contributes valuable insights into effective teaching strategies for ADHD students.